Mathematical modelling of brain tumour growth and therapy - Curtin, Lee (2019)
Glioblastoma multiforme (GBM) is the most aggressive primary brain tumour with an expected median survival of just 15 months post-diagnosis in spite of treatment. GBMs are highly invasive, such that their cells can be found in low densities far away from the apparent tumour edge indicated by magnetic resonance imaging (MRI). It is this invasiveness that can limit the efficacy of surgery. However, surgery acts as a unique opportunity for further local drug delivery which is currently not exploited as a standard of care.